Safety Guideline: Skin Antisepsis for Central Neuraxial Blockade. Issue 4 (December 2015) - Campbell, J.P.; Plaat, F.; Checketts, M.R.; Bogod, D.; Tighe, S.; Moriarty, A.; Koerner, R.
Abstract : ( Anaesthesia . 2014;69(11):1279–1286)